Keragaman Genetik Varietas Kelapa Sawit (Elaeis guineensis Jacq.) - Rahmawati, Aulia (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Oil palm (Elaeis guineensis Jacq.) is one of the leading national commodities because of its large contribution to the Indonesian national economy. In the plantation industry, palm oil is known as a commodity that has high value because it is an ingredient for producing palm oil. The genetic diversity of Indonesian oil palm accessions is currently very low. In an effort to increase genetic diversity, germplasm exploration has been carried out at the genetic diversity center of oil palm. In addition to exploration, other efforts have been made to increase genetic variation by introduction. Oil palm is a type of plant that comes from the Arecaceae family. Oil palm plants usually grow on peat soil types spread across the islands of Sumatra, Kalimantan and Sulawesi. This is a type of plant that has a fairly high level of risk of being attacked by pests. In its distribution, there are two types of oil palm that are usually cultivated by farmers, namely Elaeis guineensis Jacq., and Elaeis oleifera. Differences in properties can be seen from the morphology of the oil palm fruit endocarp ehich has different levels of thickness as a form of genetic diversity. Oil palm varieties are distinguished by the thickness of the endocarp, and also by the color of the fruit. Based on the thickness of the endocrap, oil palm is divided into three types, namely Pisifera, Dura, and Tenera. If based on the color of the fruit, there are Nigrescens, Virescens, and Albescens. One of the methods that can be used for genetic analysis is Random Amplified Polymorphic DNA (RAPD).Keywords: diversity, accession, endocarp, palm oil